Teacher social competence, student learning motivation, and learning outcomes in English subject - Ainy, Qurrot; Pratama, Hendi (ELT Forum: Journal of English Language Teaching, 2020)
This study aimed to investigate the correlation between teacher social competence, student learning motivation, and learning outcomes in English subject. The population of this study is all the students of Junior High School 1 Purbalingga academic year 2019/2020. The sample in this study is 90 students. The sampling technique is stratified convience sampling. In collecting data, there were some research instruments used; questionnaires and documentation. The research data were analyzed by Peason product-moment correlation. Based on the analysis and statistical quantification, it was found that the results of the study were (1) there is a positive and significant correlation between teacher social competence and student learning outcomes as shown by the value of Pearson correlation coefficient 0.919; (2) there is a positive and significant correlation between student learning motivation and student learning outcomes as shown by the value of Pearson correlation coefficient 0.908; (3) there is a positive and significant correlation between teacher social competence and student learning motivation as shown by the value of Pearson correlation coefficient 0.994. In conclusion, teachers’ social competence correlation is higher than students learning motivation. Therefore, the teachers should work on their social skill to improve student learning outcomes. On the other hand, the students needs to motivate themselves.